The first benthic insects (Ephemeroptera and Coleoptera) from the Upper Cretaceous of Colombia. (April 2022) - Alfonso-Rojas, Andrés; Cadena, Edwin-Alberto
Abstract: The Upper Cretaceous fossil record of insects in northern South America is almost unknown. Here we describe two fossil insects from the Chipaque Formation of (Cenomanian–Santonian), from central Colombia, representing the first report of fossil arthropods for the Upper Cretaceous of Colombia, and the first fossil record of a mayfly and beetle for northern South America. Although the specimens lack key anatomical features for a high-resolution taxonomic identification, we were able to attribute one of the specimens to Ephemeroptera and a second specimen to Coleoptera. This fossil finding opens the possibility for future discoveries of additional insect fossils in northern South American rock sequences that could fill the extensive gap that exists in this paleontological field.